Functional State of Bone Marrow-Derived Mesenchymal Stem Cells After Incubation with Silver Nanoparticles - Volkova, N.A.; Yukhta, M.S.; Pavlovich, M.S.; Goltsev, A.N. (Nanophotonics, Nanooptics, Nanobiotechnology, and Their Applications. NANO 2018. Springer Proceedings in Physics, vol 222. Springer, Cham. https://doi.org/10.1007/978-3-030-17755-3_19, 2019)
Despite of silver nanopaticles’ (AgNPs) widespread use, there is a serious lack of information concerning the toxicity of AgNPs to humans and their key cellular actions. The aim of the present study was an effect of different concentrations of 40 nm AgNPs and time of incubation on the viability, CD 44 expression, mitochondrial state, and apoptotic/necrotic processes in bone marrow-derived mesenchymal stem cells (MSCs). The obtained results suggested that 1-hour incubation with AgNPs in the concentrations of 2 and 4 μg/ml did not affect the viability and content of CD44-positive cells, as well as did not cause the development of necrosis/apoptosis processes and alteration of mitochondrial activity in MSCs. After AgNPs’ addition in the concentrations of 6 and 10 μg/ml there were a decrease of mitochondrial activity, percentage of viability cells and an increase of the number of apoptotic cells compared with the control samples of MSCs. An increase in the period of incubation with AgNPs (4–10 μg/ml) up to 1 day leads to a toxic effect on MSCs, which was manifested in the decrease of viability, content of CD44-positive cells (AgNPs 10 μg/ml), mitochondrial activity, and activation of apoptosis and necrosis. The obtained results are related to the field of applied nanotechnology, which extends to clinical medicine, especially in the development of addressed drug delivery to the target cells or organs.
Volkova, N.A., Yukhta, M.S., Pavlovich, E.V., Goltsev, A.N. (2019). Change in Functional State of Bone Marrow-Derived Mesenchymal Stem Cells After Incubation with Silver Nanoparticles. In: Fesenko, O., Yatsenko, L. (eds) Nanophotonics, Nanooptics, Nanobiotechnology, and Their Applications. NANO 2018. Springer Proceedings in Physics, vol 222. Springer, Cham. https://doi.org/10.1007/978-3-030-17755-3_19
Keywords: Mesenchymal stem cells; Silver nanoparticles; Mitochondria; Apoptosis; Necrosis; Cytofluorometry; In vitro; 7AAD; Annexin; Inhibition; Suspension